1999
DOI: 10.1039/a808006b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of photodecarbonylated ruthenium(II) complexes—potential intermediates for mixed ligand complexes

Abstract: Irradiation of solutions containing complexes of the type [RuL(CO) 2 Cl 2 ] where L is a 2,2Ј-bipyridine analogue leads to monodecarbonylation and the formation of dimeric ruthenium(II) complexes, [RuL(CO) 2 Cl] 2 , for which two different structures have been established, viz. with a trans disposition of bridging and terminal chlorides [L = di(2pyridyl) ketone] or with CO trans to bridging chlorides (L = 1,10-phenanthroline).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 12 publications
6
36
0
Order By: Relevance
“…All of the Ru-N and Ru-Cl bond distances (2.02-2.07 Å and~2.43 Å, respectively) are within the expected ranges and comparable to those observed for the related complex [Ru(phen)(CO)Cl 2 ] 2 . [42] Hydrogenation/Hydrogenolysis Activity Studies As shown in Table 3 (entries 1-6), compounds 1-4 are all active catalysts for the hydrogenation of FFR in ethanol, exhibiting essentially 100% conversion of FFR and near-complete selectivity for FFA formation at modest temperatures. cis-[Ru(6,6′-Cl 2 bpy) 2 (OH 2 ) 2 ](CF 3 SO 3 ) 2 (1) displayed better selectivity than cis-[Ru(6,6′-Cl 2 bpy) 2 (OH 2 ) 2 ](BArF) 2 (2) for C=O bond (versus C=C bond) hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…All of the Ru-N and Ru-Cl bond distances (2.02-2.07 Å and~2.43 Å, respectively) are within the expected ranges and comparable to those observed for the related complex [Ru(phen)(CO)Cl 2 ] 2 . [42] Hydrogenation/Hydrogenolysis Activity Studies As shown in Table 3 (entries 1-6), compounds 1-4 are all active catalysts for the hydrogenation of FFR in ethanol, exhibiting essentially 100% conversion of FFR and near-complete selectivity for FFA formation at modest temperatures. cis-[Ru(6,6′-Cl 2 bpy) 2 (OH 2 ) 2 ](CF 3 SO 3 ) 2 (1) displayed better selectivity than cis-[Ru(6,6′-Cl 2 bpy) 2 (OH 2 ) 2 ](BArF) 2 (2) for C=O bond (versus C=C bond) hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…In extended reactions the second carbonyl as well as the chlorides can be replaced [7b]. Without suitable strongly coordinating solvent or ligand, the irradiation can still result in the loss of a carbonyl but in such case it is typically followed by the formation of dimeric [RuCl 2 -(bpy)(CO)] 2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the first method, the labile CO ligands are substituted by the application of heat, [109] while in the second, decarbonylation takes place by irradiation with UV light. [110] Other widely studied synthetic routes are based on synthesising Ru(NN 1 )(NN 2 )Cl 2 intermediates, by using different precursors such as RuCl 3 ·xH 2 O, [107] Ru(DMSO) 4 -Cl 2 [111] or [Ru(η 6 -arene)Cl 2 ] 2 [96] as starting materials and subsequent sequential introduction of chelate ligands under different reaction conditions (Figure 19). …”
Section: Synthesis Of Ruthenium Tris-heteroleptic Complexesmentioning
confidence: 99%